2004
DOI: 10.1164/rccm.200307-973oc
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β1 Promoter Polymorphism C–509T Is Associated with Asthma

Abstract: Transforming growth factor-beta1 (TGF-beta1) is increased in the lungs of individuals with asthma and may modulate airway inflammation and remodeling. Some genetic studies have found that a C-to-T single-nucleotide polymorphism (C-509T) in the TGF-beta1 gene promoter may be associated with altered gene expression and asthma phenotype. To build on these data, we performed a case-control association study at this locus involving 527 subjects with asthma and 170 control subjects without asthma. All individuals we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
191
5
7

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(212 citation statements)
references
References 27 publications
9
191
5
7
Order By: Relevance
“…Indeed, the magnitude of the effect was similar to other regulatory polymorphisms such as the SNP in SLC22A associated with rheumatoid arthritis and loss of transcriptional activity (41) and the variant CD14 and TGF-␤ promoters (29,42). Because the functional effects of individual polymorphisms may be small, risk for complex diseases is substantially increased by synergism between multiple SNPs arrayed along a single regulatory pathway.…”
Section: Discussionmentioning
confidence: 56%
“…Indeed, the magnitude of the effect was similar to other regulatory polymorphisms such as the SNP in SLC22A associated with rheumatoid arthritis and loss of transcriptional activity (41) and the variant CD14 and TGF-␤ promoters (29,42). Because the functional effects of individual polymorphisms may be small, risk for complex diseases is substantially increased by synergism between multiple SNPs arrayed along a single regulatory pathway.…”
Section: Discussionmentioning
confidence: 56%
“…However, the genotypes associated with more severe CBD and sarcoidosis are the same ones which have been associated with lower TGF-␤ levels in previous studies (11,33). This might suggest that TGF-␤1 is not playing a role in fibrogenesis, but instead may be playing a role in immune regulation of these granulomatous diseases.…”
Section: Discussionmentioning
confidence: 68%
“…TGFβ1 has been found to modify the development and severity of asthma. [14][15][16] Although 2 studies did not demonstrate a gene-environment interaction between secondhand smoke exposure in the home and TGFβ1 in the development of asthma, 17,18 detection of interactions in common chronic lung diseases such as asthma may be hampered by etiologic heterogeneity. It may be easier to detect subtle interactions affecting disease severity using a continuous variable, and patients with CF often perform pulmonary function tests on a quarterly basis yielding the continuous variable outcome of FEV 1 .…”
Section: Commentmentioning
confidence: 99%
“…TGFβ1 was selected for study because genotypic variants of TGFβ1 have been shown to modify the severity of CF [11][12][13] and the development and/or severity of other chronic respiratory tract conditions, including asthma [14][15][16][17][18] and chronic obstructive pulmonary disease. [19][20][21] …”
mentioning
confidence: 99%